Zadanie 3. Rozwiąż równanie.
a) (x - 4) (6 - 2x) (9 + x) = 0
b) (3 + 2x) (3x2 - x - 2) = 0



Odpowiedź :

Magda

Odpowiedź:

[tex]a)\\\\(x-4)(6-2x)(9+x)=0\\\\x-4=0\ \ \ \ \vee\ \ \ \ 6-2x=0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ 9+x=0\\\\x=4\ \ \ \ \ \ \ \ \vee\ \ \ \ -2x=-6\ \ /:(-2)\ \ \ \ \vee\ \ \ \ x=-9\\\\x=4\ \ \ \ \ \ \vee\ \ \ \ x=3\ \ \ \ \ \ \vee\ \ \ \ x=-9[/tex]

[tex]b)\\\\(3+2x)(3x^2-x-2)=0\\\\3+2x=0\ \ \ \ \vee\ \ \ \ 3x^2-x-2=0\\\\2x=-3\ \ /:2\\\\x=-\frac{3}{2}\\\\\\3x^2-x-2=0\\\\3x^2+2x-3x-2=0\\\\x(3x+2)-(3x+2)=0\\\\(3x+2)(x-1)=0\\\\3x+2=0\ \ \ \ \ \ \ \ \vee\ \ \ \ x-1=0\\\\3x=-2\ \ /:3\ \ \ \ \vee\ \ \ \ x=1\\\\x=-\frac{2}{3}\\\\\\x=-\frac{3}{2}\ \ \ \ \vee\ \ \ \ x=-\frac{2}{3}\ \ \ \ \vee\ \ \ \ x=1[/tex]